2003
DOI: 10.1377/hlthaff.22.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Disclosure Practices: Results Of A National Survey

Abstract: New patient safety standards from JCAHO that require hospitals to disclose to patients all unexpected outcomes of care took effect 1 July 2001. In an early 2002 survey of risk managers at a nationally representative sample of hospitals, the vast majority reported that their hospital's practice was to disclose harm at least some of the time, although only one-third of hospitals actually had board-approved policies in place. More than half of respondents reported that they would always disclose a death or seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 21 publications
3
83
0
3
Order By: Relevance
“…Because this behavior occurs infrequently [10][11][12][13][14][23][24][25] and because we wanted to stimulate discussion and hear a range of experiences, focus groups 26 were used to explore this topic.…”
Section: Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this behavior occurs infrequently [10][11][12][13][14][23][24][25] and because we wanted to stimulate discussion and hear a range of experiences, focus groups 26 were used to explore this topic.…”
Section: Methods Designmentioning
confidence: 99%
“…[10][11][12][13][14] When disclosure does take place, patients' expectations are often not met. 15,16 Disclosure of medical errors to patients and families is widely endorsed by medical professional associations, ethicists, and patient safety experts.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most commonly cited barrier to disclosure and apology by physicians and risk managers is fear of litigation or legal liability [13,30]. At the same time, however, the link between the risk of litigation and willingness to disclose has not been established.…”
Section: Barriers To Apologies After Medical Errormentioning
confidence: 99%
“…This suggests that although disclosure and apology may result in an increased volume of claims [49], total costs may decrease. Other hospitals (for example, University of Michigan Health System, Johns Hopkins, Children's Healthcare of Atlanta, Boston's Dana Farber Cancer Institute, and Massachusetts' Sturdy Memorial Hospital) as well as private insurers (eg, COPIC) report similar experiences [12,30,61].…”
Section: Effective Apologiesmentioning
confidence: 99%
“…Medical malpractice premiums have skyrocketed in recent years, most significantly in specialties such as obstetrics-gynecology and neurosurgery, and as a result many physicians fear that every patient is a potential litigant [2]. Two national surveys designed to assess attitudes toward disclosure revealed that fear of litigation was the primary reason for both physicians' and hospitals' reluctance to disclose errors and unanticipated outcomes [3,4].…”
Section: The Risks Of Saying "I'm Sorry"mentioning
confidence: 99%